Interest in HIV pre‐exposure prophylaxis in men who have sex with men in West Africa (CohMSM ANRS 12324 – Expertise France). Issue 10 (29th August 2018) - Coulaud, Pierre‐julien; Sagaon‐Teyssier, Luis; M'madi Mrenda, Bakridine; Maradan, Gwenaëlle; Mora, Marion; Bourrelly, Michel; Dembélé Keita, Bintou; Keita, Abdoul Aziz; Anoma, Camille; Babo Yoro, Stéphane‐Alain; Dah, Ter Tiero Elias; Coulibaly, Christian; et al.
Summary: Objective: To explore the interest in taking PrEP among Western African men who have sex with men (MSM). Methods: A cross‐sectional survey was implemented at enrolment of HIV‐negative MSM in a multiple centre community‐based cohort study in four West African countries (Mali, Côte d'Ivoire, Burkina Faso, Togo). A standardised face‐to‐face questionnaire collected data on socio‐demographic and behavioural characteristics over the previous 6 months. Descriptive analysis and multivariate logistic regression helped identify factors associated with the interest in taking PrEP. Results: Of 564 participants, 87% were interested in taking PrEP. Interest in PrEP was associated with inconsistent condom use for anal sex (adjusted odds ratio (aOR): 2.11; 95% confidence interval (CI) 1.21–3.67), transactional sex (aOR: 2.02; 95% CI 1.11–3.71), searching for male sexual partners on the Internet in the previous month (aOR: 1.86; 95% CI 1.01–3.43), having a high level of self‐esteem (aOR: 1.20; 95% CI 1.06–1.36), having at least one sexually transmitted infections at enrolment (aOR: 5.08; 95% CI 1.40–18.4) and not being aware of PrEP (aOR: 2.03; 95% CI 1.04–3.96). Participants having sex with HIV‐positive male partners (aOR: 0.28; 95% CI 0.11–0.74), those being more sexually attracted to women than to men (aOR: 0.20; 95% CI 0.07–0.89) and those reporting psychological and material support from close friends (aOR: 0.33; 95% CI 0.15–0.73) were less interested in taking PreP. Conclusions: Western African HIV‐negative MSM appear very interested in taking PrEP, especially those most at risk of HIV infection. PrEP implementation in a comprehensive prevention package should be considered urgently.